Multi-lumen capillary based trypsin micro-reactor for the rapid digestion of proteins. Issue 20 (17th September 2018) - Currivan, S. A.; Chen, W. Q.; Wilson, R.; Sanz Rodriguez, E.; Upadhyay, N.; Connolly, D.; Nesterenko, P. N.; Paull, B.
Abstract : In this work we evaluated a novel microreactor prepared using a surface modified, high surface-to-volume ratio multi-lumen fused silica capillary (MLC). Abstract : In this work we evaluated a novel microreactor prepared using a surface modified, high surface-to-volume ratio multi-lumen fused silica capillary (MLC). The MLC investigated contained 126 parallel channels, each of 4 μm internal diameter. The MLC, along with conventional fused silica capillaries of 25 μm and 50 μm internal diameter, were treated by (3-aminopropyl)triethoxysilane (APTES) and then modified with gold nanoparticles, of ∼20 nm in diameter, to ultimately provide immobilisation sites for the proteolytic enzyme, trypsin. The modified capillaries and MLCs were characterised and profiled using non-invasive scanning capacitively coupled contactless conductivity detection (sC 4 D). The sC 4 D profiles confirmed a significantly higher amount of enzyme was immobilised to the MLC when compared to the fused silica capillaries, attributable to the increased surface to volume ratio. The MLC was used for dynamic protein digestion, where peptide fragments were collected and subjected to off-line chromatographic evaluation. The digestion was achieved with the MLC reactor, using a residence time of just 1.26 min, following which the HPLC peak associated with the intact protein decreased by >70%. The MLC reactors behaved similarly to the classical in vitro or in-solution approach, but provided a reduction in digestion time, and fewer peaks associated with trypsin auto-digestion, which is common using in-solution digestion. The digestion of cytochrome C using both the MLC-IMER and the in-solution approach, resulted in a sequence coverage of ∼80%. The preparation of the MLC microreactor was reproducible with <2.5% RSD between reactors ( n = 3) as determined by sC 4 D.